Impact of Mental Lexicon on Reading Comprehension in Children Growing up in Poverty - Ferroni, Marina (2020)
Objetive. This study analyses the impact that lexical representations of Spanish-speaking children in contexts of poverty have on the reading comprehension skills. Method. To this end, an assessment was made of the reading comprehension of 61 children. The results helped identify two groups within the sample: one with a high level of comprehension, and a second with a low level of comprehension. Each group’s vocabulary (semantic representations of the mental lexicon) and reading level (orthographic representations of the mental lexicon) was then assessed. Other important skills related to comprehension were likewise explored, such as working memory, inference-making ability, and morphosyntactic processing of spoken language. Results. The results provide evidence regarding the substantial impact of mental lexicon representations on reading comprehension.